A Strategic Framework (Swot Analysis Construct) for the Future of Secretarial Profession in Nigeria - Oborah, James Omatule (Journal of Office Administration : Education and Practice, 2021)
With regards to the pessimistic and optimistic divides on the future of secretarial profession in Nigeria and anchored on the strength-based theory of professional development, the study constructed a strategic framework using SWOT analysis for the future of secretarial profession in Nigeria. Online survey was conducted on the secretarial educators and practitioners and the data analysed with descriptive and inferential statistics. The results revealed the SWOT construct indicating that the secretarial profession is formidable in curriculum contents, but weak in inclusiveness, state-of-the-art instructional facilities and equipment, adequate human teaching and technical resources and enrolment. In addition, advancement in technology, innovations and professionalisation are some opportunities for sustainable future, although there are threats of interlopers, economic downturn, new technology and government policy. Stakeholders should brace up to mitigating the negative impact of these threats by continuous review of curriculum, provision of the state-of-the-art technology and updated government policy on secretarial professional practice in Nigeria